2001
DOI: 10.1067/mva.2001.111975
|View full text |Cite
|
Sign up to set email alerts
|

Failure of exclusion of internal iliac artery aneurysms

Abstract: The exclusion of IIA aneurysm did not reliably result in thrombosis of the aneurysm. For IIA aneurysms extending deeply into the pelvis, even if the size of the aneurysm is smaller than 3.0 cm, the exclusion procedure should not be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…More recently, with the increased use of endovascular surgical techniques iliac aneurysms have been managed successfully without the need for open elective surgical repair. Proximal ligation or exclusion alone is ineffective in the treatment of these aneurysms and ultimately in preventing rupture [12]. It has been shown that thrombosed aneurysms occurring spontaneously or surgically induced still have the potential for rupture since the presence of the thrombus within the aneurysm did not lower the mean arterial pressure transmitted to the arterial wall [13].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, with the increased use of endovascular surgical techniques iliac aneurysms have been managed successfully without the need for open elective surgical repair. Proximal ligation or exclusion alone is ineffective in the treatment of these aneurysms and ultimately in preventing rupture [12]. It has been shown that thrombosed aneurysms occurring spontaneously or surgically induced still have the potential for rupture since the presence of the thrombus within the aneurysm did not lower the mean arterial pressure transmitted to the arterial wall [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of bilateral internal iliac artery occlusions, the adequacy of the inferior mesenteric artery (IMA) may be assessed intraoperatively by measuring the stump pressure. Reconstruction of the IMA, when the stump pressure index (IMA pressure/radial artery pressure) is less than 0.6, helps prevent postoperative ischemic colitis [16].…”
Section: Treatmentmentioning
confidence: 99%
“…Operative treatment of patients with an isolated internal iliac artery aneurysm may consist of proximal ligation only, proximal plus distal ligation, aneurysmectomy with graft interposition, or endoaneurysmorrhaphy [15, 16]. Proximal ligation may be considered when the aneurysm is located deep in the pelvis, during repair of a ruptured common iliac artery aneurysm, if the aneurysm is densely adherent to pelvic organs, or in the presence of severe calcification.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Die ledigliche Ligatur oder Übernähung der Arteria iliaca interna am Abgang mit Belassen des möglicher-weise weiterhin über Seitenäste perfundierten Aneurysmas stellt keine sichere Sanierung dar, sekundäre Rupturen sind in der Literatur beschrieben [8,12]. Auf eine vollständige Resektion des Aneurysmasacks sollte wegen der Gefahr einer Venenverletzung verzichtet werden.…”
Section: Diskussionunclassified